EFEKTIVITAS TEKNIK KNEADING DAN COUNTERPRESSURE TERHADAP PENURUNAN INTENSITAS NYERI KALA I FASE AKTIF PERSALINAN NORMAL DI RSIA BUNDA ARIF PURWOKERTO TAHUN 2011 - Hastami, Rina sri; ., Asiandi; Handayani, Rohmi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Pain during labor is a physiologic process. Non-pharmacological therapy can be used to reduce pain during labor as massage is kneading and counterpressure technique. Women who get massage metodh during labor has decreased anxiety, pain reduction was significantly shorter. This study aims to compare the effect of kneading and counterpressure massage technique to decrease the intensity of pain the first stage of the active phase of normal deliveries before and after intervention. Type of research is a quasi-experiments that are two-group pretest posttest design comparrison. Analysis of the data used is dependent t-test and t-independent. The study was conducted at 60 maternal first stage of active phase is divided into two groups, 30 people were treated with kneading technique and 30 people were treated with counterpressure technique. From the dependent t test result on the kneading group there is a difference M ± SD = 2.00 ± 0.983, the counterpressure group differences M ± SD = 2.14 ± 1,383. It can be concluded there was significant difference between pain intensity before and after a massage (p = 0,000). While theindependent t test result on the reduction of pain intensity differences between groups obtained after the massage done t(df) = 0,889(58) and p = 0,379. There was no significant difference in the mean reduction in pain intensity of the first stage the active phase of normal deliveries are done kneading and counterpressure technique. Nevertheless counterpressure more advisable to reduce labor pain the first stage of the active phase due to work directly on neural pathways for the perception of labor pain. Key word : labor pain, massage, kneading technique, counterpressure technique.